Significance of DMBT1 in Papillary Thyroid Carcinoma Concurrent With Hashimoto’s Thyroiditis - Gan, Xiao-xiong; Li, Ya-yi; Li, Si-jin; Mo, Shi-sen; Feng, Jian-hua; Shen, Fei; Cai, Wen-song; Lai, Ye-qian; Xu, Bo (Frontiers in Oncology, 2021)
Background Papillary thyroid carcinoma (PTC) concurrent with Hashimoto’s thyroiditis (HT) was associated with a better clinical prognosis. This study aimed to investigate a potential mRNA gene that affects the development of PTC, which helps PTC concurrent with HT patients have a better prognosis. Material/Methods PTC data were obtained from The Cancer Genome Atlas (TCGA) database. And the validation data of tissue specimens were collected from Guangzhou First People’s Hospital. The thyroid tissue sections were hybridized with deleted in malignant brain tumor 1 (DMBT1) probes by situ hybridization. Survival rates were analyzed using Kaplan-Meier curves, and the log-rank test was used to compare group survival rates. Prognosis clinicopathological factors were analyzed by Cox regression. Gene Ontology (GO) and Kyoto Gene and Genomic Encyclopedia (KEGG) pathway enrichment analyses were performed using single-sample gene set enrichment analysis (ssGSEA). Finally, the correlation of deletion in DMBT1 expression with overall immune status, tumor purity, and human leukocyte antigen (HLA) gene expression profile was analyzed. Results HT was significantly associated with sex, tumor foci, extrathyroidal extension (ETE), residual tumor, and tumor stage (T stage). Moreover, PTC concurrent with HT had a lower risk of recurrence versus non-HT groups. A total of 136 differentially expressed mRNAs (DEMs) were identified between HT and non-HT groups. Among them, the expression level of DMBT1 in HT groups was statistically higher than that in non-HT groups. A significant association with ETE and recurrence was revealed in the high expression and the low expression of DMBT1. Furthermore, DMBT1 was an independent predictor of survival. The overall immune activity of high expression of DMBT1 was higher than that of the low-expression group. Conclusions The PTC patients with HT had better behavior features and prognosis than those with simple PTC. DMBT1 in PTC-HT patients was a potential possible factor that inhibits tumors. High expression of DMBT1 may improve PTC prognosis by immune-related pathways.